Наслідки недотримання права на приватність у мережі Інтернет: міжнародний аспект - Булавіна, С.; Давидова, Т.; Bulavina, S.; Davydova, Т. (Волин. нац. ун-т. ім. Лесі Українки, 2020)
Стаття присвячена подвійній проблемі, що виникла у зв’язку з широким застосуванням Інтернету, в якому, з одного боку, реалізуються права і свободи людини, надається можливість втілити низку «супутніх» прав (права на свободу думок, на освіту, на інформацію тощо), а, з іншого, спричиняється їх порушення. Аналізується міжнародна правова база захисту і забезпечення прав і свобод людини в Інтернеті, права на приватність, порушення якого може призводити до кібербулінгу, що набув офіційного статусу в Європі. The article deals with an equivocal problem that has arisen with the widespread use of the Internet, which, on the one hand, provides human rights and freedoms, an opportunity to realize a number of the «related» rights (rights to freedom of thought, education, information, etc.) and, on the other hand, causes their violation. The article analyzes the international legal framework for the protection and enforcement of human rights and freedoms on the Internet, the right to privacy, the violation of which may lead to cyberbullying, which has acquired official status in Europe. The study argues that the right to Internet access or freedom to connect (unimpeded access to it), which is gradually gaining the status of a fundamental human right due to its prevalence rate, involves other fundamental rights protection (right to life, information, liberty and security of a person, freedom of speech and thought, etc.), including implementation of the new generation rights – the right to anonymity and the right to be forgotten.
Violation Consequences of the Right to Privacy on the Internet: International Aspect
Keywords: міжнародне право; право на приватність; кібербулінг; права і свободи людини; теорія держави і права; новітні права; international low; right to privacy; cyberbullying; human rights and freedoms; theory of state and law; modern rights; 342.721